The Teaching Philosophy of the Kingdom of Saudi Arabia - Mofareh A., Alqahtani (Advances in Social Sciences Research Journal, 2019)
Any philosophy of teaching stems from the given educational system and is reliant on the principles of various educational theories. As such, the factors which inform the teaching system objectives, foundations, standards adopted by the teacher, the methods and strategies which determine individual teaching practice, inhere attitudes and/or policies for student engagement with both educational methodology and moral values. These are​harnessed to transit knowledge and improve student achievement in accordance with the fundamentals of contemporary teaching methods. In short, a teaching philosophy refers to the overall intellectual vision and a comprehensive view of strategic teaching objectives which are ultimately developed to promote the best learning outcomes. Since teaching philosophy rests on the three main and interrelated axes of the teacher, the student, and the curriculum, it is clearly imperative to involve the students in the research and discussion during the lesson. Moreover, the philosophy of teaching includes additional educational means such as the use of advanced projector devices to access the concept of the subject as quickly as possible, and the preparation of research papers by students. This study aims to introduce the student to organized academic research as an assignment of discussion, to enable them to adopt special ideas and/or express views clearly in tandem with the dissemination of information and the benefits acquired by each student, to use modern technology within the process of teaching by means of the latest audio visual aids, and to encourage students to use them in the process of submitting their papers. In order to achieve these objectives, the study seeks to investigate the following guiding questions: a) what is the basis for the Saudi Arabian philosophy of teaching?; and b) how can such a teaching philosophy be developed and managed to realize the desired results? In order to fully address these questions, a variety of research methodologies and instruments has been selected, including teacher and student questionnaires, data and document analysis, interviews with teachers, students, and educational policy-makers, and an historical contextualization of all relevant documentation. To this end, the researcher engaged with the analytical model of teaching philosophy and a number of previous studies which were used in the same context. In addition, by identifying the problem, importance, and objectives of the research, the hypotheses were deemed integral to certain teaching philosophy predicates and the ensuing results. In addition to a number of recommended stakeholder tools which address the main challenges to the teaching philosophy within Saudi Arabia, the researcher also underscored the concept of teaching philosophy as the foundation of the entire educational system to achieve all goals and targets set in accordance with a multi-dimensional philosophical vision.